PENEGAKAN HUKUM TERHADAP ANAK YANG MEMBAWA ATAU MENYIMPAN SENJATA TAJAM DI WILAYAH HUKUM POLRESTA YOGYAKARTA - Ibadata, Tekun (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Children are the greatest treasure of a nation, the survival of a nation is determined by the quality of existing children and how the child grows both in terms of character, mental and spiritual. Today there are many juvenile delinquency, ranging from violations to criminal acts, one of which is the crime of carrying and storing sharp weapons. The police as the bearer of security and law enforcement functions are required to be able to prevent, enforce the law, and formulate future regulatory patterns against the crime of carrying and storing sharp weapons by children. From the results of the study, it can be concluded, regarding the prevention efforts carried out by the Yogyakarta Police with pre-emptive, preventive, and repressive actions. Law enforcement efforts through non-penal media are carried out by pre-emptive and preventive law enforcement, while law enforcement with penal media is repressive by conducting an investigation process in accordance with applicable laws and regulations. The pattern of law enforcement in the future is to formulate pre-emtive and preventive activities as well as repressive law enforcement as a fair solution to problems and the enforcement of children's rights.